Structural Topology Optimization of Brake Disc Using the Equivalent Moving Load Method - Shengfang Zhang; Jian Yin; Yu Liu; Fujian Ma; Zhihua Sha; Dapeng Yang (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
During the braking process, the brake disc is subjected to the moving load. The process-point of the moving load moves along a certain trajectory, which makes it difficult to design the brake disc structure by using a traditional topology optimization method. The novel Equivalent Moving Load (EML) method proposed in this paper aims to solve this problem. According to the principle of continuous photographing technology, a mathematical model was established by using the round inward polygonal approximation algorithm. The EML method equalizes the continuous dynamic load action to many finite working conditions by geometric approximation. These working conditions are placed along the trajectory. The structure of the brake disc is then optimized by the EML method. Additionally, the influence of the layout style of the brake pads and the total number of working conditions on the optimization result are discussed in this paper. The optimization results showed that the new structure is a three-annulus structure. The weight of the new structure is reduced by 57.95% compared to the initial structure by structural topology optimization using the EML method. It was proved that structural topology optimization using the EML method is efficient in optimizing a structure subjected to dynamic load.